2014
DOI: 10.1063/1.4862966
|View full text |Cite
|
Sign up to set email alerts
|

Hall effect and the magnetotransport properties of Co2MnSi1-xAlx Heusler alloys

Abstract: Structural and magnetic properties of quaternary Co2Mn1-xCrxSi Heusler alloy thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…A minimum in the resistivity curve was found near 40 K, which was followed by an upturn at lower temperatures. Such a behavior has been reported in many Heusler alloys [84] and is typically attributed to the disorder enhanced coherent scattering of conduction electrons [79]. It was found that for some alloys, such a minimum has been explained on the basis of Kondo effect [85].…”
Section: A Cofemnz (Z = Si and Ge) Alloysmentioning
confidence: 84%
See 1 more Smart Citation
“…A minimum in the resistivity curve was found near 40 K, which was followed by an upturn at lower temperatures. Such a behavior has been reported in many Heusler alloys [84] and is typically attributed to the disorder enhanced coherent scattering of conduction electrons [79]. It was found that for some alloys, such a minimum has been explained on the basis of Kondo effect [85].…”
Section: A Cofemnz (Z = Si and Ge) Alloysmentioning
confidence: 84%
“…In addition to the contributions mentioned above, a term representing the structural disorder with a temperature dependence of T 1/2 is also present in systems with non-negligible disorder [84]. Keeping all the above points in mind, Bainsla et al [7] analyzed the resistivity data by performing the fitting in two different temperature regions, i.e., between 5 and 85 K and between 85 and 300 K. The resistivity trend was found to fit well with the relation, ρ (T) = ρ0 -AT 1/2 + BT 2 + CT 9/2 in the low temperature region, while the best fit is given by ρ (T) = ρ0 + DT + ET 7/ 2 in the high temperature region.…”
Section: A Cofemnz (Z = Si and Ge) Alloysmentioning
confidence: 99%
“…While electron-magnon scattering is absent in the case of true halfmetals, T 1/2 dependence reflects the contribution due to the disorder. 28 Fitting of the resistivity data has been carried out in two different temperature regions, i.e., between 5 and 85 K and between 85 and 300 K. In the low temperature region, the resistivity fits well with the relation, ρ (T) = ρ 0 -AT 1/2 + BT 2 + CT 9/2 , while in the high temperature region, the best fit is given by ρ (T) = ρ 0 + DT + ET 7/2 . In the low temperature regime, T 1/2 term dominates over the other two contributions due to the presence of disorder.…”
mentioning
confidence: 99%
“…Heusler alloys 28 and is typically attributed to the disorder enhanced coherent scattering of conduction electrons. 29 Resistivity behavior has been analyzed in the temperature range of 5 -300 K by considering different scattering mechanisms.…”
mentioning
confidence: 99%
“…Recently, Co-based Heusler alloys have attracted intense attention as potential candidates for spintronic devices due to their high Curie temperature and half-metallic electronic structure [5,27]. Reported AHE studies on Co-based Heusler alloys include bulk, granular film, bilayer, or trilayer systems, such as bulk Co 2 MnSi 1-x Al x [28], Co 2 FeSi-Al 2 O 3 granular films, Co 2 MnAl, Co 2 FeSi, Co 2 FeAl, Co 2 MnGe, and Co 2 MnSi monolayers [6,[29][30][31], Pt/Co 2 FeAl bilayer [32], or MgO/Co 2 MnGa/Pd trilayer [33]. In our previous report, a large PMA was realized in Pd/Co 2 MnSi/MgO trilayer, which was attributed to the interfacial orbital hybridization adjacent to the Heusler alloy Co 2 MnSi layer, namely, Pd/Co 2 MnSi and Co 2 MnSi/MgO interfaces [34].…”
Section: Introductionmentioning
confidence: 99%